2002
DOI: 10.1063/1.1491178
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic electron tunneling across magnetically active interfaces in cuprate and manganite heterostructures modified by electromigration processes

Abstract: We report a study of the electron tunneling transport in point-contact junctions formed by a sharp Ag tip and two different highly correlated oxides, namely, a magnetoresistive manganite La 0.66 Ca 0.34 MnO 3 and a superconducting cuprate LaBa 2 Cu 3 O 7-x . Strong chemical modifications of the oxide surface (supposedly, oxygen ion displacements) caused by applying high voltages to the junctions have been observed. This effect is believed to be responsible for an enormous growth of inelastic tunneling processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 11 publications
0
6
0
5
Order By: Relevance
“…Як вже зазначалося вище, переходи Джозефсона надпровідникбар'єр-надпровідник (S-B-S) демонструють велику кількість незвичайних (для стандартної електроніки) ефектів [4][5][6]. Запропонована з самого початку концепція ефекту Джозефсона як явища тунелювання куперівської пари електронів крізь потенційний бар'єр вже через рік після публікації оригінальної статті отримала своє експериментальне підтвердження.…”
Section: вступunclassified
See 2 more Smart Citations
“…Як вже зазначалося вище, переходи Джозефсона надпровідникбар'єр-надпровідник (S-B-S) демонструють велику кількість незвичайних (для стандартної електроніки) ефектів [4][5][6]. Запропонована з самого початку концепція ефекту Джозефсона як явища тунелювання куперівської пари електронів крізь потенційний бар'єр вже через рік після публікації оригінальної статті отримала своє експериментальне підтвердження.…”
Section: вступunclassified
“…Запропонована з самого початку концепція ефекту Джозефсона як явища тунелювання куперівської пари електронів крізь потенційний бар'єр вже через рік після публікації оригінальної статті отримала своє експериментальне підтвердження. Первісну ідею Джозефсона пізніше дещо модифікували, коли встановили, що надпровідний струм через бар'єр джозефсонівського переходу реалізується процесами андріївського відбивання квазічастинок на інтерфейсах [5]. У джозефсонівському контакті таке перетворення на межі надпровідника S та нормального металу N (бар'єра) падаючого електрону у відбиту дірку забезпечує бездисипативний транспорт заряду всередині енергетичної щілини.…”
Section: вступunclassified
See 1 more Smart Citation
“…23 Such situation has been frequently observed in disordered perovskite oxides, high T C cuprates and various CMR manganites. 24 With increasing thickness of the tunneling barrier, hopping along chains of localized states is favored. While hopping along localized states path, a carrier does not cross quantummechanically the entire distance between the electrodes, but rather jumps from the junction electrode to the first state, lose the phase memory, moves to the second nano-island and, eventually, after completing all the hopping path, jumps to the opposite electrode.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Further investigations [6] have confirmed the presence of the effect in a high-T c superconductor BiSrCaCuO and showed that it is observed up to room temperature. Experiments performed on four-component Mnbased compounds revealed the presence of resistive switchings in this class of materials as well [7,8].…”
Section: Resistive Switching Phenomenon In Transition-metal Oxidesmentioning
confidence: 99%